The Effect of Save The Last Word For Me Method - Albert Efendi Pohan; Devi Andriyani (English Department, University of Riau Kepulauan, Batam,Indonesia, 2017)
The objective of the study is to find out the effect of using save the last word for me method toward students’ writing skill for the eighth grade students’ at SMPN 36 Batam in academic year 2016/2017. The kind of this study was quantitative research. The research design was experimental design. In this study focused on quasi experimental design. The population of this study was all students for the eighth grade at SMPN 36 Batam in Academic Year 2016/2017 consist of 270 students. The sampling technique was purposive sampling. Then, the total number of sample was 60 students that consisted of 30 students of class VIII.6 who were taught by using Save The Last Word For Me method and 30 students of class VIII.4 who were taught by using Think Pair Share method. The data was collected by test. The data was analyzed by using normality test, homogeneity test and hypothesis test. The result showed that the t-observed was 2.97 and the t-table was 2.002. It means that t-observed was higher than t-table. Therefore, alternative hypothesis () was accepted and null hypothesis () was rejected. The research found that there was a significant effect of using Save The Last Word For Me method toward students’ writing skill for the eighth grade students’ at SMPN 36 Batam in academic year 2016/2017